Entomocomplex of onions in the Right-Bank Forest-Steppe of Ukraine - Kudla, V.; Tkalenko, G.; Ignat, V. (Quarantine and plant protection, 2022)
Goal. To monitor the phytosanitary condition of onion crops in the Right-Bank Forest-Steppe of Ukraine and to establish the species composition of dominant pests. Methods. The research was carried out in accordance with the generally accepted methodological recommendations in entomology. Results. As a result of long-term monitoring of onion crops, 12 species of phytophages from the ranks of Coleoptera — 46.2%, Lepidoptera — 23.1%, Diptera — 15.4%, Thysanoptera — 10.4%, Orthoptera — 5.0% and others. In the phase of leaf development (main shoot) (ВВСН 1—19) the most harmful are soil-dwelling pests: larvae of Agriotes sputator L. and Agriotes lineatus L.; larvae of the Melolontha melolontha L., the Melolontha hippocastani F), the Amphimallon solstitialis L.; Scotia segetum Schiff. and Gryllotalpa gryllotalpa L. In the phase of the beginning of thickening of the base of the leaves — bulb formation (ВВСН 41—43) phytophages dominate: onion fly (Delia antique Mg.), onion trips (Trips tabaci Lind.), Ceuthorrhynchus jakovlevi Schulzer. Conclusions. It was studied that with the number of soil pests 1.5—2.8 specimens/m2, plant damage is 24.6—28.3%, which is the reason for the liquefaction of crop density. It has been established that significant damage to onion crops is caused by the onion fly (Delia antique Mg.), the period of harmfulness of which lasts throughout the growing season. During the years of research, the flight of the phytophagous adult took place in the third decade of April — first decade of May, at the sum of active CAT temperatures (> 5°C) = 104—131°С. Mass flight of the pest was observed in the II—III decades of May, at an average daily air temperature of 12.8—17.4°C.